2004
DOI: 10.1073/pnas.0308478100
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and contraction of the hepatitis B virus transcriptional template in infected chimpanzees

Abstract: We have previously shown that hepatitis B virus (HBV) replication is controlled by noncytolytic mechanisms that depend primarily on the effector functions of the CD8 ؉ T cell response, especially the production of IFN-␥ in the liver. The mechanisms that control the nuclear pool of viral covalently closed circular DNA (cccDNA) transcriptional template of HBV, which must be eliminated to eradicate infection, have been difficult to resolve. To examine those mechanisms, we quantitated intrahepatic HBV cccDNA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
209
1
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(228 citation statements)
references
References 31 publications
12
209
1
2
Order By: Relevance
“…As HBV polymerase inhibitors do not have a direct effect on cccDNA formation, the decreased intrahepatic cccDNA levels are supposed to be derived from the lack of sufficient recycling of viral nucleocapsids to the nucleus because of the strong inhibition of viral DNA synthesis in the cytoplasm and less incoming viruses from the blood. Furthermore, experiments with HBVreplicating transgenic mice 9 and chimpanzees 10,11 have shown that inflammatory cytokines can efficiently suppress viral replication through noncytolytic immune-mediated mechanisms that also contribute to diminishing the cccDNA reservoirs of infected cells. However, these processes may require a very long time, given the long half-life of both hepatocytes and cccDNA in the absence of cell division.…”
Section: Nfection With Hepatitis B Virus (Hbv) Causes Acutementioning
confidence: 99%
“…As HBV polymerase inhibitors do not have a direct effect on cccDNA formation, the decreased intrahepatic cccDNA levels are supposed to be derived from the lack of sufficient recycling of viral nucleocapsids to the nucleus because of the strong inhibition of viral DNA synthesis in the cytoplasm and less incoming viruses from the blood. Furthermore, experiments with HBVreplicating transgenic mice 9 and chimpanzees 10,11 have shown that inflammatory cytokines can efficiently suppress viral replication through noncytolytic immune-mediated mechanisms that also contribute to diminishing the cccDNA reservoirs of infected cells. However, these processes may require a very long time, given the long half-life of both hepatocytes and cccDNA in the absence of cell division.…”
Section: Nfection With Hepatitis B Virus (Hbv) Causes Acutementioning
confidence: 99%
“…Since hepadnavirus infection is not cytopathic, elimination of hepadnavirus-infected hepatocytes requires immune attack by virus antigen-specific CTLs, leading to the elimination of cccDNA directly by hepatocyte death or indirectly during compensatory hepatocyte proliferation [6]. Whether significant cccDNA loss occurs in the absence of hepatocyte turnover (i.e., hepatocyte death and compensatory proliferation) remains unclear [7]. We and others have reported that resolution of transient hepadnavirus infections involves immunemediated attack on large numbers of hepatocytes and significant turnover of the hepatocyte population [6,8], with turnover of up to 10% of the hepatocyte population per day [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…As in humans, some of the foci of virus-free hepatocytes in the woodchuck liver clearly represent FAH, often considered to be preneoplastic [34][35][36][37][38], whereas virus-free hepatocytes in other foci appear to have a normal morphology [36]. In contrast, virtually all hepatocytes can be infected during a typical transient WHV infection [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it has been amply demonstrated that termination of acute hepadnavirus infections in the woodchuck (7,12) and chimpanzee (9)(10)(11) systems is associated with the destruction of infected cells and hepatocellular regeneration (7)(8)(9)(10)(12)(13)(14)(15). On the other hand, it is equally clear from chimpanzee (9)(10)(11) and transgenic mouse (16,17) experiments, that HBV replication is strongly inhibited by the antiviral effects of inflammatory cytokines produced by HBVspecific CD8 ϩ T cells when they recognize antigen in the infected or transgenic liver. Furthermore, it has been shown that viral clearance in acutely infected chimpanzees is heralded by a sharp drop in the HBV DNA content of the liver, which depends on the influx of IFN-␥-producing CD8 ϩ T cells into the liver (10), but which precedes and is out of proportion to the amount of liver disease (10).…”
mentioning
confidence: 99%
“…Although it is generally agreed that viral clearance and disease pathogenesis during HBV infection are mediated by the immune response (2-6), the extent to which cytopathic and noncytopathic CD8ϩ T cell antiviral functions contribute to these events is a matter of some debate (7-11). On the one hand, it has been amply demonstrated that termination of acute hepadnavirus infections in the woodchuck (7, 12) and chimpanzee (9-11) systems is associated with the destruction of infected cells and hepatocellular regeneration (7)(8)(9)(10)(12)(13)(14)(15). On the other hand, it is equally clear from chimpanzee (9-11) and transgenic mouse (16,17) experiments, that HBV replication is strongly inhibited by the antiviral effects of inflammatory cytokines produced by HBVspecific CD8 ϩ T cells when they recognize antigen in the infected or transgenic liver.…”
mentioning
confidence: 99%